Purification of the mother liquor sugar from industrial stevia production through one-step adsorption by non-polar macroporous resin. (15th February 2019) - Liu, Yaxian; Hua, Xiao; Wang, Mingming; Yang, Ruijin
Highlights: Purified MLS of high quality and resource utilization was got by nonpolar resin. Adsorption of impurity or SG on nonpolar resin was tuned by ethanol concentration. SG was adsorbed by nonpolar resin in 25% ethanol while impurity was unadsorbed. Static adsorption reduced impurity from 34.13% to 12.88% with SG recovery of 86%. Dynamic adsorption reduced impurity from 34.13% to 4.78% with SG recovery of 90%. Abstract: Steviol glycosides (SGs)-enriched mother liquor sugar (MLS) used to be considered as a by-product of industrial stevia production. This work developed an efficient purification strategy to remove impurities from MLS. A non-polar macroporous adsorption resin (MAR) NDR-1 was selected as the adsorbent and ethanol solution was used as the mobile phase. The adsorption ratio of SGs and impurities was highly affected by ethanol concentration (v/v) due to the polarity difference and competition. In particular, in 25% (v/v) ethanol solution, SGs were mostly adsorbed on NDR-1 while impurities were completely dissolved in ethanol solution. After static adsorption in 25% ethanol solution and desorption in pure ethanol, the impurity content of MLS was decreased from 34.15% to 12.88%, with a high adsorption ratio of 92.24%. At the same condition, dynamic adsorption presented a better purification result with low impurity content of 4.78% and high SGs recovery rate of 89.88%.